Penyusunan Perangkat Pembelajaran Pendidikan Agama Hindu Di Sekolah Dasar Dengan Integrasi Penguatan Pendidikan Karakter - Rikayana, I Kadek (Jayapangus Press, 2021)
Character education is an educational approach that aims to shape good values, ethics and morals in students. Values such as honesty, caring, discipline, and responsibility are considered important to form a strong and ethical character in society. This study aims to find out how the preparation of learning tools for Hinduism education in elementary schools with the integration of strengthening character education. This study adopts a qualitative approach, utilizing literature study or desk study as the main technique in collecting information. The integration of character education in Hindu Religious Education in Primary Schools is important to shape students' character. Teachers play a key role in implementing this approach. The development of learning tools that include planning, materials, teaching methods, and evaluation of student character is a complex step. Evaluation that includes control of other factors helps understand the effectiveness of this approach. Values-based approaches, stories, active participation, art, and reflection are useful strategies. Teachers have an important role as examples and leaders in shaping student character. Hindu Religious Education in elementary schools can be an effective tool to shape noble and responsible character in students.